Phytochemical Analysis and Nanoparticles-Based Bioactivity Screening of Five Medicinal Plant Extracts - Yamani, Hanaa Abbas; Othman, Abrar; Gashgari, Rukaia (Discoveries in Agriculture and Food Sciences, 2023)
This study investigated the presence of bioactive phytochemical compounds in five medicinal plant extracts using nanoparticles. Silver nanoparticles were synthesized using aqueous extracts of five medicinal plants including Juniperus excelsa, Moringa oleifera, Prosopis juliflora, Pithecellobium dulce, and Eucalyptus globulus. The plants were randomly collected from the cities of Jeddah and Taif, Kingdom of Saudi Arabia. The total polyphenolic contents of plant extracts were determined through GCMS and HPLC. The nanoparticle synthesizing efficiency of plant extracts was also examined and XRD, UV-Vis spectroscopy, and zeta potential measurements were performed for nanoparticle characterization. The nanoparticle formation rate was assessed through UV-Vis spectroscopy. The results confirmed the antimicrobial efficacy of examined plant extracts and suggested their potential application for infectious disease treatments.